2020
DOI: 10.24875/ric.19003184
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Index in Patients with Resectable Esophageal Squamous Cell Carcinoma: Fibrinogen/Prealbumin Ratio

Abstract: Background: Fibrinogen (Fib) to albumin (ALB) fibrinogen-to-albumin ratio as a prognostic index for esophageal cancer has been confirmed. A novel prognostic index was initially proposed with fibrinogen to prealbumin ratio (FPR) in patients with resectable esophageal squamous cell carcinoma (ESCC). Objective: The objective of the study was to study the prognostic role of the novel prognostic index (FPR) in patients with resectable ESCC without any neoadjuvant treatment. Methods: In this retrospective study, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…26 In addition, similar conclusions have been drawn in digestive system tumors such as gastric cancer, pancreatic cancer, esophageal cancer, and so on: the prognosis of patients tends to become worse with the increase of FPR. 14,27,28 Some researchers believe that the combined score of FPR and PNI can predict the prognosis of elderly patients with gastric cancer, but FPR is not an independent prognostic factor for elderly patients with gastric cancer, which is different from our results. 15 Additionally, in the subgroup analysis, we employed univariate and multivariate Cox analyses to mitigate the influence of confounding factors, delving deeper into the significance of FPR in predicting prognosis across different subsets of gastric cancer patients.…”
Section: Discussioncontrasting
confidence: 99%
“…26 In addition, similar conclusions have been drawn in digestive system tumors such as gastric cancer, pancreatic cancer, esophageal cancer, and so on: the prognosis of patients tends to become worse with the increase of FPR. 14,27,28 Some researchers believe that the combined score of FPR and PNI can predict the prognosis of elderly patients with gastric cancer, but FPR is not an independent prognostic factor for elderly patients with gastric cancer, which is different from our results. 15 Additionally, in the subgroup analysis, we employed univariate and multivariate Cox analyses to mitigate the influence of confounding factors, delving deeper into the significance of FPR in predicting prognosis across different subsets of gastric cancer patients.…”
Section: Discussioncontrasting
confidence: 99%
“…that FPR can evaluate the prognosis of malignant tumors such as colorectal cancer, hepatocellular carcinoma, esophageal cancer and gastric cancer (13)(14)(15)35). A recent meta-analysis pointed out that high value of FPR is associated with poorer survival and increased risk of recurrence in cancer patients (36).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more biomarkers are needed to help guide therapy and improve the accuracy of prognostic determinations for individual patients. As a novel serological prognostic marker, multiple studies have demonstrated that FPR can evaluate the prognosis of malignant tumors such as colorectal cancer, hepatocellular carcinoma, esophageal cancer and gastric cancer ( 13 15 , 35 ). A recent meta-analysis pointed out that high value of FPR is associated with poorer survival and increased risk of recurrence in cancer patients ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation